Pengaruh Layanan Informasi Terhadap Kepuasan Siswa dalam Memanfaatkan Layanan Bimbingan Konseling di SMK Paisubatu - wiesmayani salma (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2024)
The purpose of the research is to find out student satisfaction in utilizing guidance and counseling services. This research is a quantitative research. The sample in this study is 15 students. Data collection in this study uses questionnaire and documentation techniques. Data analysis techniques are carried out including UIJ, prerequisites, analysis, and hypothesis testing. The results of the study show that information services have a strong and significant positive relationship with student satisfaction in utilizing counseling guidance services at SMK Paisubatu, this is evidenced by the results of the linearity test where the value obtained is 0.735 where this value is greater than 0.05. This is also shown by the results of a simple linear regression analysis where the equation obtained is Y = 23.334 + 0.418 X where the coefficient X is 0.418 and has a positive value. This positive value indicates a unidirectional relationship, which means that if the information service variable rises by one unit, it will be